Answer:
x = 3
Step-by-step explanation:
3(2x + 5) = 33
3 * 2x + 3 * 5 = 33
6x + 15 = 33
6x = 33 - 15
x = 18 / 6
x = 3
The answer is c i hope this help you out.
Answer:
b
Step-by-step explanation:
1: y=8, (-2,8)
2: y=6, (-1,6)
3: y=0, (2,0)
Step-by-step explanation:
Insert the x value into each equation then see what value of y that you need to get 4 on the right hand side of the equation.
9514 1404 393
Answer:
- left 1 unit
- down 2 units
Step-by-step explanation:
The transformation g(x) = f(x -h) +k is a translation of f(x) to the right by h units and up k units.
1. h = -1, so the graph of g(x) is the graph of f(x) shifted left 1 unit. (blue)
__
2. k = -2, so the graph of g(x) is the graph of f(x) shifted down 2 units. (green)